The Education Effects Of The "Ketuk Pintu Waspada Tb" Program On Knowledge And Attitude Of Tuberculosis Transmission Prevention In Banjarsari Kulon, Sumbang - Anggiyani, Santi; Muzaenah, Tina (Jurnal Ilmiah Wahana Pendidikan, 2024)
Tuberculosis (TB) is a lung disease caused by Mycobacterium tuberculosis bacteria transmitted through droplets/saliva. To prevent and break the chain of TB transmission, it is essential to have good knowledge and attitude towards TB prevention. Education activities of the "Ketuk Pintu Waspada TB" program serve as a strategic step in improving knowledge and attitude towards TB transmission prevention in the community. This research aims to determine the effects of education in the "Ketuk Pintu Waspada TB" program on knowledge and attitude towards TB transmission prevention. Method: This quantitative study with a pre-experimental design used a one-group pretest-posttest design. The population in this research is all households (KK) in Banjarsari Kulon Village, Sumbang District, with a sample of 50 respondents using the Cluster Sampling technique with the sampling fraction per cluster formula. Data were analyzed using the Wilcoxon test. Results: Knowledge and attitude showed significant results for each with (p = 0.0001). Education significantly affected knowledge and attitude towards TB transmission prevention. Respondent characteristics showed that the majority were aged 20-30 years (38%), with the majority being female (56%). Most respondents had a primary education level (38%), and most were housewives (34%). Conclusion: Education in the "Ketuk Pintu Waspada TB" Program affects knowledge and attitude towards TB transmission prevention in Banjarsari Kulon Village, Sumbang.